2015
DOI: 10.4085/1062-6050-50.4.06
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Ankle Instability and Neural Excitability of the Lower Extremity

Abstract: Context: Neuromuscular dysfunction of the leg and thigh musculature, including decreased strength and postural control, is common in patients with chronic ankle instability (CAI). Understanding how CAI affects specific neural pathways may provide valuable information for targeted therapies.Objective: To investigate differences in spinal reflexive and corticospinal excitability of the fibularis longus and vastus medialis between limbs in patients with unilateral CAI and between CAI patients and participants ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 43 publications
0
46
0
Order By: Relevance
“…7,8 Similarly, Kosik et al 9 reported deviations in cortical mapping and excitability of the fibularis longus with the use of transcranial magnetic stimulation among patients with CAI compared with healthy control participants. These studies [7][8][9] have contributed to the concept of altered neural pathways after ligamentous injury.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…7,8 Similarly, Kosik et al 9 reported deviations in cortical mapping and excitability of the fibularis longus with the use of transcranial magnetic stimulation among patients with CAI compared with healthy control participants. These studies [7][8][9] have contributed to the concept of altered neural pathways after ligamentous injury.…”
mentioning
confidence: 99%
“…The long-term disability associated with CAI may also demonstrate some of these CNS changes, including altered neural mapping and corticalactivation changes. 7,8 Individuals with CAI demonstrated smaller motor-evoked potentials, as well as deficits in motor thresholds, providing insight into how the descending pathways from the brain activate the ankle's musculature to control movement. 7,8 Similarly, Kosik et al 9 reported deviations in cortical mapping and excitability of the fibularis longus with the use of transcranial magnetic stimulation among patients with CAI compared with healthy control participants.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, ankle sprain injury is likely to be associated with alterations in alpha motor neuron excitability [17] and previous research has shown that CAI participants activate their peroneus longus (PL) prior to HS earlier than non-injured controls [9]. This early activation may coincide with a decrease in the excitability of spinal reflexes of the lower extremity [18,19] and may prevent normal medial displacement of the center of pressure during the stance phase of gait, resulting in individuals with CAI bearing weight more laterally on their foot (and increasing total frontal plane displacement) [9]. Participants with a history of ankle sprain have previously been shown to apply greater loading through the lateral column of their foot during the latter part of stance [23,32].…”
mentioning
confidence: 99%
“…Multiple sensorimotor deficiencies have been observed in patients with a history of LAS, 92 and changes in cortical and spinal pathways among populations with CAI have been documented. [93][94][95][96][97][98][99] These alterations may help to explain many of the disease and patient-reported deficiencies observed during clinical examination but are currently limited to laboratory techniques. It is possible that in the coming years, this emerging body of information may influence the comprehensive assessments of patients with LAS.…”
Section: Prediction Models and Additional Considerationsmentioning
confidence: 99%